The Archetypes in the Undercurrent of Ernest Hemingway’s Novels - GONCHAR-KHANJYAN, NATALYA (Bulletin of Yerevan University B: Philology, 2021)
The literature of the XX century has involved numerous Greek-Roman mythological, as well as biblical topics and characters, imparting modern meanings to them. These topics and characters, in different modern metamorphoses, are manifested as an “open text” in a series of already classical works; meanwhile, in many other cases, the mythological archetypes, allusions enrich the undercurrent and context (Joice, T. Wolf, Faulkner, Saroyan, etc.). This is what we observe in the prose of the eminent master of undercurrent Ernest Hemingway, in particular: in his novels “Fiesta” and “Farewell to Arms”.